2018
DOI: 10.1002/jcb.27951
|View full text |Cite
|
Sign up to set email alerts
|

Activation of mammalian terget of rapamycin kinase and glycogen synthase kinase‐3β accompanies abnormal accumulation of cholesterol in fibroblasts from Niemann‐Pick type C patients

Abstract: Background Niemann Pick type C (NPC) lysosomal disorder is linked to the disruption of cholesterol transport. Recent data suggest that the molecular background of this disease is more complex. It was found that accumulation of cholesterol and glycolipids in the late endosomal/lysosomal compartment of NPC1 cells may affect mitochondrial functions. Materials and Methods In this study, primary skin fibroblasts derived from skin biopsies of two anonymous patients with NPC‐carrying mutations in the NPC1 gene, chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Accordingly, increased ROS, cellular stress and mitochondrial dysfunction have all been associated with NPC (Yambire, Fernandez-Mosquera et al, 2019). Moreover, aberrant lipid droplet formation (Onal, Kutlu et al, 2017) may also be linked to autophagy defects described in NPC (Castellano & Thelen, 2017, Liao et al, 2007, Sarkar et al, 2013, Wos et al, 2019. Our proteomic analysis identified autophagosome formation and maturation as the most affected pathway in microglia upon loss of NPC1.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Accordingly, increased ROS, cellular stress and mitochondrial dysfunction have all been associated with NPC (Yambire, Fernandez-Mosquera et al, 2019). Moreover, aberrant lipid droplet formation (Onal, Kutlu et al, 2017) may also be linked to autophagy defects described in NPC (Castellano & Thelen, 2017, Liao et al, 2007, Sarkar et al, 2013, Wos et al, 2019. Our proteomic analysis identified autophagosome formation and maturation as the most affected pathway in microglia upon loss of NPC1.…”
Section: Discussionmentioning
confidence: 72%
“…Additionally, lipid accumulation within lysosomes and mitochondrial membranes may induce oxidative stress (Wos, Szczepanowska et al, 2016, Yu, Gong et al, 2005. Different studies linked NPC1 dysfunction to alterations in mammalian target of rapamycin complex 1 (mTORC1) and microtubule-associated proteins 1A/1B light chain 3B (LC3) signaling, suggesting that autophagy might be compromised in NPC (Castellano & Thelen, 2017, Ko, Milenkovic et al, 2005, Liao, Yao et al, 2007, Wos, Komiazyk et al, 2019. Although peripheral organs such as liver and spleen are affected by the disease, restoring NPC1 function in the central nervous system (CNS) prevents neurodegeneration and premature lethality of the Npc1 -/mouse (Loftus, Erickson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Each of the three isoforms (Akt1, Akt2 and Akt3) display a high degree of sequence homology but differ slightly in the localization of their regulatory phosphorylation sites and expression distribution. Studies in NPC1 patient fibroblasts have reported decreased phosphorylation of Akt [ 40 ]. Analysis of liver transcriptome revealed decreased expression of Akt2 in Npc1 −/− mice [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study of urinary stem cells from patients of mitochondrial encephalopathy, lactic acidosis, and stroke-like episodes shows a decrease in GSK3B phosphorylation, which would correlate with increased activity, but the total levels of GSK3B were not measured, and therefore it is not clear if the protein is indeed active ( 55 ). In contrast, human fibroblasts with mutations in NPC1, which result in lysosomal cholesterol storage, show an increase in the inhibitory phosphorylation on GSK3B, and therefore decreased GSK3B activity ( 56 ). While this result needs to be tested in a more systematic manner, it is possible that the differential activation of GSK3B by mitochondrial and lysosomal defects contributes to the opposite regulation exerted over the transcription of genes encoding cholesterol synthesis enzymes.…”
Section: Discussionmentioning
confidence: 99%